OA38 From service delivery to community enablement: a public health approach to palliative care. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - McLoughlin, Kathleen; Rhatigan, Jim; Richardson, Marie; Lloyd, Rebecca
Abstract : Milford Care Centre is the only hospice in Ireland to make a strategic decision to embrace a public health approach to palliative care, through the development, implementation and evaluation of the Compassionate Communities Project. This presentation seeks to examine why Milford made the decision to move toward a community enablement model, describes the development and implementation of the Compassionate Communities Project to date, presents key findings from recent evaluations and highlights our plans for the future. The presentation uses a reflective, story telling approach to meet it's aims, coupled with data and statistics gathered from the evaluations, and includes a new short film 'Tell Me' developed by recent Computer Science graduates for the Project to use to engage with communities during Café Conversations. The presentation will highlight the relevance of Health Promoting Palliative Care theory to the development of a three-tier model of programme activity, examine the challenges in implementing such an approach and will discuss the impact of upstream intervention to downstream service provision using case studies.